Going to Santri International through Upgrade English Productive Skills of Students Islamic Boarding School - Fitrah Aulia Anshar; Yeasy Agustina Sari; Nurul Puspita; Bagus Usada; Umar Al Faruq A. Hasyim; Suhono Suhono; Fahrur Rozi (Bulletin of Community Engagement, 2023)
Islamic boarding schools. However, in contrast to modern Islamic boarding schools, affiliated with Nahdlatul Ulama (NU) prioritize moral education rather than foreign language skills, especially English. Therefore, to face this challenge, the students must be able to master foreign languages ​​including English. English became the Lingua Franca in the MEA era. The Importance of English Language Proficiency in English is expected that students would be able and ready to go international. Therefore, English language skills must be owned by students. Furthermore, this service community activity aims to improve Santri in English skills which include; Speaking, Listening, Reading and Writing. The subjects assisted by this activity are Islamic boarding school students in Metro City who are members of the English Club. This activity uses Participatory Action Research (PAR). It is hoped that this activity can improve their English skills. Based on the results of community service activities (PKM) English language learning assistance for students at Universitas Ma’arif Lampung Metro is an effective strategy to improve capabilities English speaking students. It can be seen in the results of the participants' responses to the training feedback and evaluation sessions for these training activities are new things for them so that they can add and broaden their horizons, and through this activity, trainees can train their writing, speaking, reading and listening skills Keywords: English Productive Skills, Santri International, Community English Skills